Development of Apron for Florists by Rath Chombhuphan and Vinai Taravet - Chombhuphan, Rath; Taravet, Vinai (Dusit Thani College Journal, 2020)
The research employed a mixed method research. The objectives were: Development of Apron for Florists. The population and sample group used in this research were 130 florists in Bangkok and its surrounding provinces by sample random sampling. Step 1. Quantitative research studied by 130 florists in Bangkok and its vicinity. By using the questionnaire, data analysis with mean, percentage, and standard deviation. Step 2: Qualitative research May The in-depth data collection was conducted by using a semi-structured interview form with 3 experienced florists. Content Analysis A Study for the Development of Apron for Florists. The results of the questionnaire show are as follows: 1) Florists have knowledge about 2) The florist is happy and has good hygiene at work. 3) The florist has chosen the characteristics of the appropriate fibers to produce aprons for the florists. Is at a good level. 4) The florists analyzed the characteristics of the characteristics of aprons for the florists at a good level. From the in-depth interview from 3 florists in accordance with the survey results from the questionnaire It was found that the florists wanted to use cotton to make aprons for the most florists and the design of the aprons. It was found that the florists needed an apron that was designed to be suitable for their shape and comfortable to use, which can be used to produce an apron that meets the requirements for a florist.